Penyuluhan Kesehatan Pencegahan Kanker Payudara dan Pemeriksaan Payudara Sendiri (SADARI) pada Mahasiswi di Institusi Pendidikan Non Kesehatan di Kota Padang - Leni Merdawati; Boby Febri Krisdianto; Rika Fatmadona; Esi Afrianti; Reni Prima Gusty (Warta Pengabdian Andalas, 2019)
The incidence of breast cancer in Indonesia is around 8,625 cases and found that 82% of breast cancer patients are already at an advanced stage. Breast cancer patients do not yet know how to detect cancer early and are reluctant to conduct an early examination. West Sumatra is a province with the second highest incidence rate after Yogyakarta. In an effort to reduce mortality from breast cancer an effective screening program is needed to find out early. This activity aims to provide education and health information about breast cancer prevention and breast self-examination (BSE) or SADARI as an initial step in early detection of breast cancer. The method used was simulation, audio-visual education and demonstration. This activity was expected to be able to increase the knowledge, attitudes and awareness of female students in preventing breast cancer. Results of the activity increased student knowledge about breast cancer prevention and breast self-examination. They had a positive attitude towards the prevention and early detection of breast cancer and were willing to do regular breast self-examinations every month independently. Evaluation of this activity shows that it can increase knowledge by 81% - 90% of the knowledge, attitudes and actions of female students towards breast cancer prevention and breast self-examination.